Pengaruh Pola Asuh Orang Tua Dan Kontrol Diri Terhadap Tingkat Agresif Pada Remaja - Ardiawan, Deni; Christiana, Ratih; Hamidah, Salsabila Wahyu; Kamaria, Baiq Mila; Nazhifatunnufus, Aida (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
This research aims to determine the influence of parenting patterns on the level of aggression in adolescents, as well as to determine the influence of parenting patterns and self-control on the level of aggression in adolescents. The research design uses explanatory quantitative research. The research subjects were students of SMK 1 Kuripan, SMA 5 Mataram and SMA 1 Gerung in West Lombok Regency, a total of 150 students consisting of 93 men and 57 women, carried out using a purposive sampling technique. The research procedure was carried out in 8 meetings using collaboration between the REB Group Counseling stages and the DIBS Technique stages. The research results show that the influence of parental parenting and self-control can have an aggressive influence with a percentage of 57.9%. Data analysis was carried out using path analysis, it was found that permissive parenting was positively correlated with aggressive behavior (r = 0.359, p = 0.000), authoritarian parenting was positively correlated with aggressive behavior (r = 0.384, p = 0.000), and authoritative parenting was correlated negative with aggressive behavior (r = -0.523, p = 0.000). This shows that there is a negative correlation between authoritative parenting and aggressive behavior.